Defining the boundaries and expanding the utility of head and neck cancer patient derived xenografts. (January 2017) - Swick, Adam D.; Stein, Andrew P.; McCulloch, Timothy M.; Hartig, Gregory K.; Ong, Irene M.; Sampene, Emmanuel; Prabakaran, Prashanth J.; Liu, Cheng Z.; Kimple, Randall J.
Highlights: Head and neck cancer PDXs can be generated for a wide range of tumor characteristics. A 24-h delay post surgical resection does not impact engraftment rate. Protein expression biomarkers are stable across PDX passages. Mutational profile of PDXs are stable from patient tumor to multiple PDX generations. Abstract: Background: Patient derived xenografts (PDXs) represent an essential tool in oncologic research, and we sought to further expand our repertoire of head and neck squamous cell carcinoma (HNSCC) while determining potential boundaries for this system. Methods: We consented new patients for PDX development and determined if a 24-h time delay from tumor excision to xenograft implantation affected PDX establishment. We developed a tissue microarray (TMA) from formalin fixed, paraffin embedded PDXs and their subsequent passages and carried out quantitative immunohistochemistry for EGFR, pEGFR, pAkt, pERK and ERCC1. First and last passaged PDXs were compared via a paired t -test to examine for the stability of protein expression across passages. We performed a similar comparison of the mutational profile of the patient tumor and resulting xenografts using a targeted sequencing approach. Results: No patient/tumor characteristics influenced PDX take rate and the 24-h time delay from tumor excision to xenograft implantation did not affect PDX establishment, growth or histology. There was no significant difference in biomarker expression between the first and last passaged PDXs for EGFR, pEGFR, pAkt, and ERCC1. For pERK there was a significant difference (p = 0.002), but further analysis demonstrated this only arose in three of 15 PDXs. Targeted sequencing revealed striking stability of passenger and likely driver mutations from patient to xenograft. Conclusions: The stability of protein expression across PDX passages will hopefully allow greater investigation of predictive biomarkers in order to identify ones for further pre-clinical and clinical investigation.